2023
DOI: 10.1037/pspa0000337
|View full text |Cite
|
Sign up to set email alerts
|

Under the veil of tolerance: A justification–suppression approach to anti-Islamic implicit bias in reaction to terrorist attacks.

Abstract: Twenty years after 9/11, the impact of terrorism on social and political attitudes remains unclear. Several large-scale surveys suggest that terrorism has no discernible effects on direct, self-report measures of prejudice toward Arab-Muslims. However, direct measures may lack the sensitivity to detect subtle underlying attitudes that are considered socially unacceptable to openly express. To tap these subtle reactions, we assessed more sensitive and implicit measures of the cognitive–affective aspects of prej… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 102 publications
(185 reference statements)
1
2
0
Order By: Relevance
“…It is worth noting that in a robust multiple-regression analysis that included all four malevolent traits, psychopathy was found to be the only significant predictor of shooting bias in violent video games. This result is consistent with prior research that has demonstrated the strong relationship between psychopathy and aggressive behavior in general (Paulhus et al, 2021), as well as research indicating that shooting bias in violent video games reflects impulsive and hostile reactions (Arnoult et al, 2023), and that psychopathy is significantly associated with violent video gaming (Jahic et al, 2021). Additionally, the fact that aggressive behavior in violent video games was linked to both psychopathy and serious traffic offenses in this study aligns with a wealth of research documenting a connection between violent video game play and aggression (Anderson et al, 2010).…”
Section: As Shown Insupporting
confidence: 92%
See 2 more Smart Citations
“…It is worth noting that in a robust multiple-regression analysis that included all four malevolent traits, psychopathy was found to be the only significant predictor of shooting bias in violent video games. This result is consistent with prior research that has demonstrated the strong relationship between psychopathy and aggressive behavior in general (Paulhus et al, 2021), as well as research indicating that shooting bias in violent video games reflects impulsive and hostile reactions (Arnoult et al, 2023), and that psychopathy is significantly associated with violent video gaming (Jahic et al, 2021). Additionally, the fact that aggressive behavior in violent video games was linked to both psychopathy and serious traffic offenses in this study aligns with a wealth of research documenting a connection between violent video game play and aggression (Anderson et al, 2010).…”
Section: As Shown Insupporting
confidence: 92%
“…Higher scores on this measure indicate a careless attitude toward harming innocent victims. Recent research using a similar task indicates that shooting biases are associated with greater hostility toward targets and impulsive (automatic) behavioral tendencies (Arnoult et al, 2023).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Understanding and measuring aggression has perennially posed a challenge for researchers striving to discern its origins and manifestations. The advent of digital games, marked by their immersive interactivity and controlled environments, have offered novel avenues for probing spontaneous hostile behaviors and aggressive predispositions (Arnoult et al, 2023;Correll et al, 2002) [7,11] . Recent investigations involving real-world offenders highlight a connection between aggressive behaviors in video games, the severity of committed offenses, and psychopathic traits (Ghavam et al, 2023) [14] .…”
Section: Introductionmentioning
confidence: 99%
“…Participants in the study were asked to play a video game where their objective was to "shoot" avatars represented as armed criminals, while sparing unarmed, innocent victims. This game was adapted from the work of Arnoult et al (2023) [7] . A noticeable 'shooting bias' towards unarmed characters was interpreted by the researchers as an inclination to inflict unnecessary harm on innocent figures.…”
Section: Introductionmentioning
confidence: 99%